Kampanye PR tentang BESADU sebagai Sarana Aspirasi Pengaduan di Belitung - Pratami, Nisa; Anugrah, Dadan; Wibawa, Darajat (Reputation: Jurnal Ilmu Hubungan Masyarakat, 2024)
This study aims to describe the campaign management in disseminating the Besadu program which is managed based on fact finding, campaign planning, campaign implementation and campaign evaluation conducted by the Belitung Regency Communication and Information Office. The research method used is a descriptive study with in-depth interview data collection techniques, passive participatory observation and documentation. The results of this study were carried out in four stages, namely: 1) Fact finding was carried out from monitoring through social media, 2) The campaign planning stage began with setting goals, target publics, messages, strategies, and communicators, 3) The implementation stage was carried out by direct socialization and indirect socialization and 4) The evaluation stage is carried out by looking at the increasing number and quality of complaints, the community satisfaction index, and the level of community attitude towards Besadu.